Inventing ourselves : lesbian life stories. - Farnham, Margot (London New York : Routledge, 1991)
Fonds Suzan Daniel (FSD)
First published by the Hall Carpenter Archives: Lesbian Oral History Group, 1989
Engels
Monografie